The Impact of Transformational Leadership on Affective Organizational Commitment and Job Performance: The Mediating Role of Employee Engagement - Jiatong, Wang; Wang, Zheng; Alam, Mehboob; Murad, Majid; Gul, Fozia; Gill, Shabeeb Ahmad (Frontiers in Psychology, 2022)
This study investigated the impact of transformational leadership on affective organizational commitment and job performance with the mediating role of employee engagement. This study gathered data from 845 hotel employees in China and the structural equation modeling technique was used to verify the results. The findings indicated that transformational leadership has a positive effect on affective organizational commitment and job performance. Meanwhile, results showed that employee engagement partially mediates in the relationship between transformational leadership, affective organizational commitment, and job performance. This study contributes to the research on transformational leadership in the Chinese hospitality sector and analyzes its effects on work performance metrics. Furthermore, theoretical and practical implications were also discussed in this article.